Comparison of teh performance of SD Bioline Syphilis 3.0 assay with the RPR test for the syphilis screening in Dar es Salaam, Tanzania (Tanzania Medical Journal, 2007)
Background: World Health Organization in 2003 launched Sexually Transmitted Diseases Diagnostics Initiative (SDI) with mission to promote the development, evaluation and application of sexually transmitted infection diagnostic tests including syphilis screening appropriate for use in primary health care settings in developing countries. Objective: To evaluate the performance of SD BIOLINE Syphilis 3.0 test (Standard Diagnostics Inc., South Korea) using routine serum samples from blood donors, antenatal clinic attendees and out patients.Settings: Mwananyamala and Amana District Hospitals, and Muhimbili University College of Health Sciences, Department of Microbiology and Immunology, Dar es Salaam, TanzaniaMethods: A total of 498 serum samples were initially tested on both SD BIOLINE Syphilis 3.0 and rapid plasma reagin (RPR) tests and were then confirmed on Treponema pallidum hemaagglutination (TPHA) test. Results: The overall seroprevalence of syphilis was 5.6% (28/498) on TPHA, 8.2% (41/498) on SD BIOLINE Syphilis 3.0 and 9.8% (49/498) on RPR tests. The SD BIOLINE test had higher sensitivity (79% vs. 68%) and specificity (96% vs. 94%) compared to RPR test. Conclusion: The overall sensitivity (79%) of SD BIOLINE syphilis 3.0 test found is low whereas specificity (96%) found is similar compared to the previous evaluation but higher compared to the sensitivity (68%) and specificity (94%) of the currently used RPR test. SD BIOLINE syphilis 3.0 test offers better sensitivity, specificity and test efficiency than the currently used RPR test. Recommendation: The SD BIOLINE syphilis 3.0 test offers better sensitivity, specificity, test efficiency and operational characteristics than the currently used RPR test and may be adopted for use in syphilis screening in our settings. Keywords: Screening, confirmatory assay, syphilis, Dar es Salaam, Tanzania Tanzania Medical Journal Vol. 21 (1) 2006: pp. 6-7